ANALISIS TEKSTUAL DAN KONTEKSTUAL HADIS TENTANG MENGUBAH KEMUNGKARAN DALAM HADIS ARBA’IN KARYA IMAM AN-NAWAWI - Rozi, Muhammad Syafiq; Imamuddin, Basuni (UI Scholars Hub, 2025)
Islam, as a comprehensive religion, regulates all aspects of human life including social and community aspects. Hence, one will find the Hadith about amending misdeeds in the Hadith of Arba'in. In understanding the hadith as a whole, there are two typologies of understanding tendencies, namely textual and contextual. This study aims to analyze the textual and contextual meanings of the Hadith about amending misdeeds in Hadith Arba'in by Imam An-Nawawi. The research method used is descriptive analytical method with qualitative approach. The theory used in this research is the three types of meaning according to Fayiz (in Matsna, 2016) and the classification of context according to Umar (in Kholison, 2016). The data used is the hadith about changing the evil contained in the book of Hadith Arba'in by Imam An-Nawawi. The results of the analysis show that the meaning obtained from the contextual analysis of the Hadith about amending misdeeds in Hadith Arba'in is broader than the textual analysis. This study is expected to provide a deeper understanding of the textual and contextual meanings of the Hadith about amending misdeeds in Imam An-Nawawi's Hadith Arba'in and to serve as an important reference for the Muslim community and future researchers who want to explore the linguistic richness of Islamic religious texts.